Comparative Analysis of the United States’ War on Drugs Policy in Mexico and Colombia: Failure and Success Factors - Hapsari, Renitha Dwi; Ramadhanti, Hendrina Nur Alifia; Putri, Karenina Mutiara (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
Drug smuggling activities in the United States carried out by drug cartels from Mexico and Colombia contribute to the region's instabilities. Many threats and terrorist acts that accompanied the distribution of illegal drugs left civilians in fear. The War on Drugs policy promoted by the United States, which aims to apprehend drug cartels, causes severe losses in the long run. Colombia is the only successful case. On the other hand, Mexico offers a different story despite both are countries with unstable political and weak law enforcement. The paper conducts a comparative study on Colombia and Mexico to evaluate the factors that contribute to the success and failure behind the implementation of the War on Drugs policy. The paper concludes that an aggressive approach (i.e., military) is less efficient in combatting drug smuggling activities than the developmental approach (i.e., socio-economic development)